2016
DOI: 10.1088/0953-8984/28/48/486001
|View full text |Cite
|
Sign up to set email alerts
|

Relieving geometrical frustration through doping in the Dy1−xCaxBaCo4O7swedenborgites

Abstract: The geometrically frustrated antiferromagnetic Swedenborgite DyBaCo4O7 is investigated by a combination of xray diffraction, magnetization and dielectric measurements. Systematic doping in the series Dy1−xCaxBaCo4O7 causes a lifting of the geometrical frustration resulting in a structural transition from a Trigonal P31c to an orthorhombic Pbn21 symmetry at x = 0.4. This structural transition can also be accessed as a function of temperature, and all our orthorhombic specimens exhibit this transition at elevate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…It has been shown that this is an efficient way to adjust the bond valence requirements of Ba 2+ which is strongly underbonded in this family of compounds [4,38,41] and is the driving force for the successive phase transitions. In the case of the "Ca-114" compound discussed in this work, the highest-symmetry hexagonal P6 3 mc phase is not realized, however the trigonal subgroup P31c has been only observed above 1073 K [42]. By replacing the Ln 3+ by Ca 2+ the orthorhombic Pna2 1 symmetry is favored.…”
Section: B Temperature Evolution Of Crystal Structurementioning
confidence: 69%
“…It has been shown that this is an efficient way to adjust the bond valence requirements of Ba 2+ which is strongly underbonded in this family of compounds [4,38,41] and is the driving force for the successive phase transitions. In the case of the "Ca-114" compound discussed in this work, the highest-symmetry hexagonal P6 3 mc phase is not realized, however the trigonal subgroup P31c has been only observed above 1073 K [42]. By replacing the Ln 3+ by Ca 2+ the orthorhombic Pna2 1 symmetry is favored.…”
Section: B Temperature Evolution Of Crystal Structurementioning
confidence: 69%
“…The ϵ’ ‐T studies indicate a maximum at ~360 °C, which may be indicative of a structural transition or rearrangement of the various tetrahedral moieties in the structure. It may be noted that there have been reports of a phase transition in swedenborgite compound, CaBaCo 4 O 7 , and other substituted compounds, where a change in symmetry has been observed [73] …”
Section: Resultsmentioning
confidence: 99%
“…The measurements were carried out over the 2θ range from 5 to 80 degrees, with step size of 0.026 degrees. Initially, the X′pert High score Plus software was employed for preliminary analysis, followed by refinement of the PXRD patterns using the GSAS program [10–105] . During the refinement, various parameters including lattice parameters, scale factors, background (Fourier polynomial background function), pseudo‐Voigt (U, V, W, and X), and isotropic thermal displacement factors (U iso ) were refined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation